DISCOURSES ON OLDER PEOPLE: THEMES OF SOCIAL INCLUSION - Lehoczka , Lydia (International Journal of Psychosocial Rehabilitation, 2019)
The paper contains both theoretical and empirical reflection on the problems in older people. It also addresses the issue of socially inclusive society, and the benefits of media for social inclusion and its representation in educational practice, because the study also presents the results of an analysis of the problems in older people and media images of older people which were broadcast in the TV news in Slovakia from February to April 2017.